(The Effect of Hydrochlorination of Alpha-pinena on The Yield of Camphene - Moestafa, Achmad (Balai Besar Industri Agro, 1990)
The derivation of alpha-pinene into various compound had been studied for many years. The transformation of pinene into camphene was carried out by hydrochlorination process. The process waas in fluenced by several conditions such as temperature, time of reaction and the atmospheric pressure. When the temperature and atmospheric pressure had been fixed, the time of hydrochlorination have a great effect. It was found that oversaturated condition of HCl gas reduced the camphene yield. The optimum time of hydrochlorination process was 30 minutes if 50 ml of alpha-pinene was bubble with HCl gas at the rate of 20 ml perminute on standard condition.